Eosinophilic colitis necessitating surgery: a rare case report - Pakanati, Rajababu; Uday Kiran, S.; Srikanth, Y.; Minhaaz; Sravya, V.; Hema Sundar, K. (International Surgery Journal, 2025)
Eosinophilic colitis (EC) is a rare heterogenous inflammatory disorder with a wide range of symptoms that can mimic a variety of pathologies. We report a rare case of EC presenting as recurrent intestinal obstruction. A 45-year gentleman presented with recurrent episodes of colicky abdominal pain whose blood investigations revealed eosinophilia and high absolute eosinophilic count. Abdominal radiograph and USG abdomen and pelvis were suggestive of intestinal obstruction. Computerised tomography and colonoscopy revealed ascending colon stricture, and colonoscopy-guided biopsy suggested chronic nonspecific colitis. Laparotomy revealed an obstructive lesion of the ascending colon with no regional lymphadenopathy. A right radical hemicolectomy was performed, and the histopathological examination revealed EC. The patient had an uneventful postoperative recovery and was started on medical therapy with albendazole, levocetirizine, montelukast and diethylcarbamazine. The patient has been on regular follow-up and is doing well.